ANALISIS USAHATANI PADI SAWAH MT-III PROGRAM IP 400 DI KECAMATAN WERU, KABUPATEN SUKOHARJO - Ediatama, Revy Satria; Tri Sundari, Mei; Khairiyakh, Re'faul (Universitas Jambi, 2023)
The increase in national rice production is highly necessary in line with the growing population. One of the programs aimed at increasing nationalrice production is the IP 400 program. This study aims to determine the amount of cost, revenue, income, and profit of rice farming under the IP 400 program, as well as to assess the feasibility of rice farming during the third planting season (MT-III) of the IP 400 program in Weru District, Sukoharjo Regency. The basic method used in the research is descriptive. The research location was determined purposively. The samples were selected using proportional random sampling. The data analysis methods used include. (1) farming cost analysis (2) farming revenue analysis (3)farming income analysis (4) farming profit analysis, (5) R/C ratio analysis, (6) B/C ratio analysis. This study shows that the average total cost of rice farming in the MT-III season of the IP 400 program is IDR 11,841,180/ha/season, with an average revenue of IDR 30,212,459/ha/season. Thus, the average income obtained is IDR 20,605,461/ha/season, and the average profit is IDR 18,371,279/ha/season. Based on the feasibility analysis, the R/C ratio value is 2.55 and the B/C ratio is 1.55. This indicates that rice farming in the MT-III season of the IP 400 Program in Weru District is profitable and feasible. IP 400 rice farming generates substantial earnings (R/C = 2.55; B/C = 1.55), which significantly increases farmer income. With this rise in income, farming households' economic resilience improves, so directly contributing to poverty reduction in rural areas. As a result, the government should focus on adopting policies that are suited for places with potential for lowland rice growing.